2016
DOI: 10.1002/2016ja022972
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing cometary electrons with kappa distributions

Abstract: The Rosetta spacecraft has escorted comet 67P/Churyumov‐Gerasimenko since 6 August 2014 and has offered an unprecedented opportunity to study plasma physics in the coma. We have used this opportunity to make the first characterization of cometary electrons with kappa distributions. Two three‐dimensional kappa functions were fit to the observations, which we interpret as two populations of dense and warm (density = 10 cm−3, temperature = 2 × 105 K, invariant kappa index = 10−>1000), and rarefied and hot (densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
81
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 48 publications
6
81
4
Order By: Relevance
“…However, Broiles et al (2016) found that laboratory testing could not account for all possible distortions, including spacecraft blockages, differential sensitivity between detectors, or the ageing of spacecraft components in flight. They developed a new version of the geometric factor for the electron sensor based observations made in flight, which assumes that the electron distribution is isotropic.…”
Section: N S T Ru M E N Tat I O Nmentioning
confidence: 99%
See 4 more Smart Citations
“…However, Broiles et al (2016) found that laboratory testing could not account for all possible distortions, including spacecraft blockages, differential sensitivity between detectors, or the ageing of spacecraft components in flight. They developed a new version of the geometric factor for the electron sensor based observations made in flight, which assumes that the electron distribution is isotropic.…”
Section: N S T Ru M E N Tat I O Nmentioning
confidence: 99%
“…Consequently, Clark et al (2015) concluded that the electrons must be heated by waves, and speculated that lower hybrid waves were a likely candidate. Broiles et al (2016) extended this study of the cometary electron environment at 67P by performing case studies when it was far from the Sun (∼3 au), and near perihelion (∼1.3 au). They also found that the velocity space density of cometary electrons was well fitted by the summation of two kappa functions.…”
mentioning
confidence: 99%
See 3 more Smart Citations